Toxicity Evaluation of Iodine Disinfectant Inclusion on Mortality and Growth of Artemia franciscana Nauplii - Reza Istiqomatul Hidayah; Woro Hastuti Satyantini; Sapto Andriyono (Jurnal Biosains Pascasarjana, 2023)
Artemia franciscana nauplii is a source of nutrients and pathogen vectors due to the non-selective nature of the filter feeder. Prevention of pathogens is done by adding iodine disinfectant to suppress the emergence of bacteria. One way to find out if a substance is toxic is by testing the toxicity and lethal concentration (LC50) on A. franciscana nauplii. The aim of this study was to evaluate the disinfectant effect of iodine and determine the lethal concentration of iodine in 50% of A. franciscana nauplii (LC50). Brine Shrimp Lethality Test (BSLT) method using Artemia as test animal. The results of the toxicity test with several doses of iodine showed that the toxic threshold value for 96 hours was 20.31 ppm. The results were supported by the presence of stunted growth at a dose of 100 ppm by measuring the length and weight. The conclusion of this study is that the administration of iodine at several concentrations is toxic to A. franciscana nauplii if it exceeds 20.31 ppm and affects the growth of A. franciscana nauplii.